Depression and quality of life in patients with neurological disorder in a Malaysian hospital - Das, Priscilla; Naing, Nyi Nyi; Wan Abdul Jamil, Wan Arfah Nadiah; Naing @ Noor Jan, Khin Ohnmar; Kueh, Yee Cheng; Rasalingam, Kantha (Hong Kong Academy of Medicine Press, 2019)
Objective: To investigate association between major depressive disorder (MDD) and quality of life in patients with neurological disorder. Methods: This cross-sectional study was carried out at a Malaysian hospital between April 2016 and December 2016 using convenience sampling. Patients aged ≥18 years with intracranial tumour or other brain disorders were invited to participate. Quality of life was assessed using the European Organisation for Research and Treatment of Cancer Quality of Life questionnaire version 3.0; diagnosis of MDD was made using Mini International Neuropsychiatric Interview. Results: Of 122 patients approached, 100 (66 women and 34 men) were included (response rate, 93.5%), with a mean age of 45.3 years. The prevalence of MDD in patients with neurological disorder was 30%. Compared with non-depressed patients, patients with MDD had poorer global health status / quality of life (p = 0.003), and reduced physical (p = 0.003), role (p = 0.021), emotional (p < 0.001), cognitive (p = 0.004), and social (p = 0.007) functioning, as well as more symptoms of fatigue (p = 0.004), pain (p < 0.001), dyspnoea (p = 0.033), insomnia (p < 0.001), appetite loss (p = 0.002), constipation (p = 0.034), diarrhoea (p = 0.021), and financial difficulties (p = 0.039). Conclusion: Patients with MDD had reduced quality of life. Fatigue, pain, dyspnoea, insomnia, appetite loss, constipation, diarrhoea, and financial difficulties were prevalent among patients with MDD.